Unraveling the Narrative of Gender-Based Violence in Nigerian Schools through a Thorough Literature Review - Roland-Akindele, Mary (Corpus Intellectual, 2023)
In the context of Gender and Development in the 21st Century and in alignment with SDG 16 and SDG 4, this article explores gender-based violence, (GBV) which is rooted in power dynamics driven by gender disparities. It explores the widespread but underreported issue of school related gender based violence (SRGBV). This specific emphasis on educational settings, which predominantly targets girls. This article adopts a qualitative approach and draws on reliable sources to show the complex nature of GBV. This includes violence that leaves victims with permanent scars, such as verbal, physical, and psychological abuse. According to figures from around the world, 30% of women have experienced physical or sexual violence. This statistic highlights the pervasiveness of GBV worldwide, which is a serious issue in the 21st Century. While the prevalence of SRGBV in Nigeria lacks comprehensive documentation. Findings from selected states within the country reveal a startling average of 47.1 percent of students reporting such experiences, underscoring its significance, particularly for female students who bear the brunt of this violence. Underlying the urgency of this exploration is the imperative to comprehend the profound repercussions of GBV on the educational, psychological well-being, and prospects of young girls. This article unravels the intricacies of GBV and also explores the societal attitudes and power structures that enable its persistence, reflecting the themes of Gender and Development in the 21st Century. Integral to the analysis is an exploration of the societal attitudes and power structures that facilitate the perpetuation of such violence, thereby reinforcing cycles of bias and exclusion. By examining case studies across various cultural contexts, it highlights how the gender issue intersects with factors like race, socioeconomic status, patriarchy, and geographic location, aligning with the inclusivity objectives of SDG 4. The article emphasizes the urgent need to eradicate SRGBV from educational institutions in Nigeria. Finally, the paper embraces the cooperation of policy makers, gender experts, security personnel, and educational stakeholders to establish a secure, welcoming learning environment. Additionally, the adoption of gender-responsive physical fitness skill in Nigerian schools will lessen the vulnerability of female students.